E-LAPD BASED ON PROBLEM BASED LEARNING TO IMPROVE STUDENTS' CRITICAL THINKING SKILLS - Siti Andini Ajeng Pramesti; Bertha Andini Yonata (Jurnal Eduscience)
Purpose – Development of E-LAPD based on Problem Based Learning to improve students' critical thinking skills on reaction rate material in class XI SMA which is said to be valid, practical, and effective.